2014
DOI: 10.1007/s10856-014-5211-7
|View full text |Cite
|
Sign up to set email alerts
|

Implant–abutment connections: influence of the design on the microgap and their fatigue and fracture behavior of dental implants

Abstract: Microgap between implant and abutment can produce biological and mechanical problems such as peri-implantitis and/or fatigue failures. The aim of this study was to evaluate microgap size and fatigue behavior of external and internal connections. In both systems the torque to tighten the abutment screw of single crown abutments was 45 Ncm. Fifty implants for each connection type were studied. One subgroup (n = 5) was used by the observation and evaluation of the microgap, other (n = 5) was tested for fracture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 10 publications
1
57
0
10
Order By: Relevance
“…Regarding the thickness of different components, Gil et al . showed that thicker external hexagonal connections were usually able to provide a better load distribution because of its higher resistant section . This statement is in line with the discussion presented above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the thickness of different components, Gil et al . showed that thicker external hexagonal connections were usually able to provide a better load distribution because of its higher resistant section . This statement is in line with the discussion presented above.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially pure titanium has good biocompatibility and is free of alloying elements that may be harmful to the organism, but has low mechanical strength. The possibility of implant failure is catastrophic because fracture of any implant component may compromise the long‐time performance of the device . From the patient perspective, implant failure compromises esthetical and functional recovery, with impact on self‐esteem and quality of life, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, even considering all benefits of the dental implant design evolution, interface microgap values under dynamic‐loading conditions, below bacteria dimensions, are still a challenge. Studies have shown microgaps for internal and external connection around 0.97 and 1.22 μm, respectively, that is, 5 to 6 times larger than overall bacterial size. With bacteria generally having a size of 0.2 μm in diameter and 1‐8 μm in length, this means that microbial penetration through this space is inevitable.…”
Section: Current Biomaterial‐based Solutions To Prevent Peri‐implantitismentioning
confidence: 99%